Prevalencia de consumo riesgoso y dañino de alcohol en adolescentes de nivel medio superior - Sánchez Cortés, Iván Alejandro (Universidad Michoacana de San Nicolás de Hidalgo, 2007)
The adolescence, stage of physical and psychological changes, in where they experience identity conflict. They can be surrounded in several forms with the alcohol. The alcoholism is chronic, progressive, incurable a disease and often mortal produced by the excessive etilic alcohol ingestion. The who defines the alcoholism like the daily alcohol ingestion superior to 50 gr. in woman and 70 gr. in the man. The alcoholism affects but to the adult men but this increasing to its incidence between the women and the young people. In Mexico the age group that showed a high incidence went of 18 to 29 years. According to World-wide Organization and the Health the amount of young people who consume alcohol increase in the last a 20% 10 years. At the moment the relation is of 6 men by each 4 women. According to the National Survey of Addictions of 1993, 6,4% of the population including presented/displayed at least a weekly episode of alcoholism and 11%, of one to three episodes in a month. OBJECTIVE: To determine prevalence of risky and harmful consumption of alcohol in adolescent of superior mean level. MATERIAL AND METHODS: I am made observational, descriptive study, crosssectional type survey in 315 adolescents between 14 and 19 years in Preparatory Not the 5 Melchor Ocampo of the UMSNH. Use procedure of size of sample for finite population, with design of stratified sampling or by clusters. The survey consists of three parts, first to know the sociodemographic conditions like age, sex, spirit but ingested, later a structured questionnaire is applied and self applicable AUDIT (alcohol Uses Disorder Identification Test) to know the prevalence risky and harmful consumption of alcohol and by I complete two questions referring to antecedents of ingestion of alcohol and in alcoholism the parents.

La adolescencia, etapa de cambios físicos y psicológicos, en donde experimentan conflicto de identidad. Pueden estar envueltos en varias formas con el alcohol. El alcoholismo es una enfermedad crónica, progresiva, incurable y muchas veces mortal producida por la ingestión excesiva de alcohol etílico. La OMS define el alcoholismo como la ingestión diaria de alcohol superior a 50 gr. en la mujer y 70 gr. en el hombre. El alcoholismo afecta más a los varones adultos pero esta aumentando su incidencia entre las mujeres y los jóvenes. En México el grupo de edad que manifestó una incidencia alta fue de 18 a 29 años. Según la Organización Mundial de La Salud la cantidad de jóvenes que consumen alcohol aumento un 20% en los últimos 10 años. Actualmente la relación es de 6 hombres por cada 4 mujeres. Según la Encuesta Nacional de Adicciones de 1993, un 6.4% de la población incluida presentó por lo menos un episodio semanal de embriaguez y 11%, de uno a tres episodios en un mes. OBJETIVO: Determinar la prevalencia de consumo riesgoso y dañino de alcohol en adolescente de nivel medio superior. MATERIAL Y METODOS: Se realizó estudio observacional, descriptivo, transversal tipo encuesta en 315 adolescentes entre 14 y 19 años en la Preparatoria No 5 Melchor Ocampo de la UMSNH. Se empleó procedimiento de tamaño de muestra para población finita, con diseño de muestreo estratificado o por racimos. La encuesta consta de tres partes, la primera para conocer las condiciones sociodemográficas como edad, sexo, bebida alcohólica más ingerida, posteriormente se aplica un cuestionario estructurado y autoaplicable AUDIT (alcohol Use Disorder Identification Test) para conocer la prevalencia de consumo riesgoso y dañino de alcohol y por ultimo dos
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4102; info:eu-repo/classification/cti/3; FCMB-E-2007-0002; Riesgo; Alcohol; Adolescentes